Role of bicarbonate in pH recovery from intracellular acidosis in the guinea-pig ventricular myocyte. - Lagadic-Gossmann, D; Buckler, K; Vaughan-Jones, R (1992)
1. Intracellular pH (pHi) was recorded ratiometrically in isolated guinea-pig ventricular myocytes using the pH-sensitive fluoroprobe, carboxy-SNARF-1 (carboxy-seminaphthorhodafluor). 2. Following an intracellular acid load (10 mM NH4 Cl removal), pHi recovery in HEPES-buffered Tyrode solution was inhibited by 1.5 mM amiloride (Na(+)-H+ antiport blocker). In the presence of amiloride, switching from HEPES buffer to HCO3-/CO2 (pHo of both solutions = 7.4) stimulated a pHi recovery towards more alkaline levels. 3. Amiloride-resistant, HCO(3-)-dependent pHi recovery was inhibited by removal of external Na+ (replaced by N-methyl-D-glucamine), whereas removal of external Cl- (replaced by glucuronate, leading to depletion of internal Cl-), removal of external K+, or decreasing external Ca2+ by approximately tenfold had no inhibitory effect. These results suggest that the amiloride-resistant recovery is due to a Na(+)-HCO3- cotransport into the cell. 4. The stilbene derivative DIDS (4,4'-diisothiocyanatostilbene-2,2'-disulphonic acid, 500 microM) slowed Na(+)-HCO(3-)-dependent pHi recovery. 5. Intracellular pH increased in Cl(-)-free solution and this increase still occurred in Na(+)-free solution indicating that it is not caused via Na(+)-HCO3- symport and is more likely to be due to Cl- efflux in exchange for HCO3- influx on a sarcolemmal Cl(-)-HCO3- exchanger. The lack of any significant pHi recovery from intracellular acidosis in Na(+)-free solution suggests that this exchanger does not contribute to acid-equivalent extrusion. 6. Possible voltage sensitivity and electrogenicity of the co-transport were examined by using the whole-cell patch clamp technique in combination with SNARF-1 recordings of pHi. Stepping the holding potential from -110 to -40 mV did not affect amiloride-resistant pHi recovery from acidosis. Moreover, following an intracellular acid load, the activation of Na(+)-HCO3- co-influx (by switching from HEPES to HCO3-/CO2 buffer) produced no detectable outward current (outward current would be expected if the coupling of HCO3- with Na+ were > 1.0). 7. Intracellular intrinsic buffering power (beta i) was assessed as a function of pHi (beta i computed from the decrease of pHi following reduction of extracellular NH4 Cl in amiloride-containing solution). beta i in the ventricular myocyte increases roughly linearly with a decrease in pHi according the following equation: beta i = -28(pHi) +222.6. 8. Comparison of acid-equivalent efflux via Na(+)-HCO3- symport and Na(+)-H+ antiport showed that, following an intracellular acidosis, the symport accounts for about 40% of total acid efflux, the other 60% being carried by the antiport.(ABSTRACT TRUNCATED AT 400 WORDS)